Molecular and temporal control of restimulation-induced cell death (RICD) in T lymphocytes - Lee, Katherine P.; Epstein, Benjamin; Lake, Camille M.; Snow, Andrew L. (Frontiers in Cell Death, 2023)
For effective adaptive immunity, T lymphocytes must rapidly expand and contract in an antigenspecific manner to effectively control invading pathogens and preserve immunological memory, without sustaining excessive collateral damage to host tissues. Starting from initial antigen encounter, carefully calibrated programmed cell death pathways are critical for maintaining homeostasis over distinct phases of the T cell response. Restimulation-induced cell death (RICD), a self-regulatory apoptosis pathway triggered by re-engagement of the T cell receptor (TCR), is particularly important for constraining effector T cell expansion to preclude overt immunopathology; indeed, genetic disorders affecting key molecules involved in RICD execution can manifest in excessive lymphoproliferation, malignancy, and autoimmunity. Herein we review our current knowledge of how RICD sensitivity is ultimately regulated over the course of an immune response, including recent revelations on molecules that tune RICD by enforcing resistance or promoting susceptibility in expanding versus mature effector T cells, respectively. Detailed dissection of the molecular and temporal control of RICD also illuminates novel therapeutic strategies for correcting abnormal T cell responses noted in various immune disorders by ultimately tuning RICD sensitivity.